1)
a)
4x-1=7x+14
4x-7x=14+1
-3x=14+1
-3x=15 | :(-3)
x=-5
b)
3-4 x (3x-2)=2 x (5x-3)
3-12x+8=10x-6
11-12x=10x-6
-12x-10x=-6-11
-22x=-17
x=17/22
c)
(5x-3) ² = 9
5x-3=+-3
5x-3=-3
5x-3=3 | +(-3)
5x=0
x=0
2)
a)
5x - 2 • (x+3) ≤ 3 • (2x-1)
5x-2x-6 ≤ 6x-3
3x-6 ≤ 6x-3
3x-6x ≤ -3 +6
-3x ≤ 3
x > sau egal cu -1
b)
2x -1 /2 - x-2 /5 ≥ 9x-3 /10
x-9/10 ≥ 9x-3/10
x-9x ≥ -3/10 + 9/10
-8x ≥ 3/5
x ≤ -3/40
3)
3x+ y = -1
3x= -1 - y
x= -1/3 - 1/3y
x= -1/3 - 1/3y
x+2y=3
x= 3 - 2y
x= 3 - 2y
4)
3x-y=4
3x=4 + y
x= 4/3 + 1/3y
x= 4/3 + 1/3y